Photoacoustic generation by multiple picosecond pulse excitation - Liu, Tan (American Association of Physicists in Medicine, 2010)
Purpose: The purpose of this work is to demonstrate that higher amplitude of ultrashort laser induced photoacoustic signal can be achieved by multiple-pulse excitation when the temporal duration of the pulse train is less than the minimum of the medium’s thermal relaxation time and stress relaxation time. Thus, improved signal-to-noise ratio can thus be attained through multiple-pulse excitation while minimizing the energy of each pulse. Methods: The authors used a Michelson interferometer together with a picoseconds laser system to introduce two 6 ps pulses separated by a controllable delay by introducing a path length difference between the two arms of the interferometer. The authors then employed a series of three interferometers to create a pulse train consisting of eight pulses. The average pulse energy was 11 nJ and the temporal span of the pulse train was less than 1 ns. Results: The detected peak-to-peak amplitude of the multiple-pulse induced photoacoustic waves were linearly dependent on the number of pulses in the pulse train and such a linearity held for different optical absorption coefficients. The signal-to-noise ratio improved when the number of pulses increased. Moreover, nonlinear effects were not detected and no photoacoustic saturation effect was observed. Conclusions: The authors have shown that multiple-pulse excitation improves the signal-to-noise ratio through an accumulated energy deposition effect. This method is invaluable for photoacoustic measurements that require ultrashort laser pulses with minimized pulse energy to avoid laser damage.